Analysis of Student Understanding about Teacher Competency (Personal Competence) - Mutiara Felicita Amsal; Munir Munir; Rusman Rusman; Dony Darma Sagita (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This study aims to determine the extent of student understanding of the personality and social competence of teachers. Personality competence is part of teacher competence that must be known by prospective teacher students. This study uses quantitative research methods with a sample of 173 PGSD students in the fourth semester. Based on the results of the study, it was found that 20% of the students did not understand the competence of teachers, especially the personality competencies that prospective teachers must possess to become teachers in the future. Personal competence is a competency that must be possessed by every teacher. Personality competencies do not just appear, but must be instilled since the teacher is still a teacher candidate at a teacher training college.